Ontogenetic aspects of hypertension development: analysis in the rat - Zicha, J; Kunes, J (Physiological reviews, 1999)
In this review, we attempt to outline the age-dependent interactions of principal systems controlling the structure and function of the cardiovascular system in immature rats developing hypertension. We focus our attention on the cardiovascular effects of various pharmacological, nutritional, and behavioral interventions applied at different stages of ontogeny. Several distinct critical periods (developmental windows), in which particular stimuli affect the further development of the cardiovascular phenotype, are specified in the rat. It is evident that short-term transient treatment of genetically hypertensive rats with certain antihypertensive drugs in prepuberty and puberty (at the age of 4-10 wk) has long-term beneficial effects on further development of their cardiovascular apparatus. This juvenile critical period coincides with the period of high susceptibility to the hypertensive effects of increased salt intake. If the hypertensive process develops after this critical period (due to early antihypertensive treatment or late administration of certain hypertensive stimuli, e.g., high salt intake), blood pressure elevation, cardiovascular hypertrophy, connective tissue accumulation, and end-organ damage are considerably attenuated compared with rats developing hypertension during the juvenile critical period. As far as the role of various electrolytes in blood pressure modulation is concerned, prohypertensive effects of dietary Na+ and antihypertensive effects of dietary Ca2+ are enhanced in immature animals, whereas vascular protective and antihypertensive effects of dietary K+ are almost independent of age. At a given level of dietary electrolyte intake, the balance between dietary carbohydrate and fat intake can modify blood pressure even in rats with established hypertension, but dietary protein intake affects the blood pressure development in immature animals only. Dietary protein restriction during gestation, as well as altered mother-offspring interactions in the suckling period, might have important long-term hypertensive consequences. The critical periods (developmental windows) should be respected in the future pharmacological or gene therapy of human hypertension.
Keywords: kardiovaskulární abnormality; Rats; kardiovaskulární systém; těhotenství; Hypertension; Disease Models, Animal; Cardiovascular System; krysa rodu Rattus; modely nemocí na zvířatech; ženské pohlaví; zvířata; Humans; Pregnancy; Cardiovascular Abnormalities; zpožděný efekt prenatální expozice; hypertenze; Female; Prenatal Exposure Delayed Effects; lidé; Animals